2020
DOI: 10.25081/jaa.2020.v6.6398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four irrigation doses and four varieties on agronomical characteristics and yield of cotton cultivation in central Greece

Abstract: In recent years, reduced irrigation has been applied for the cultivation of cotton. While this strategy remains desirable, it needs to be evaluated as it affects the yields and growth of cotton. During 2015 and 2016, two similar cotton experiments (Gossypium hirsutum L.) were performed in Greece, in the area of Karditsa and especially in the location of Palamas. An experiment was established designed according to split-plot design, with main plots four levels of irrigation (IRR. 2, IRR. 4, IRR. 6, IRR. 8) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown the biomass of cotton plants and their reproductive organs increase with the volume of irrigation [30]. Irrigation levels, with drip irrigation, affect the number of closed bolls (The quantity of irrigation influenced the count of closed bolls) [31]. The data was obtained at 4 irrigation levels and plots four varieties of cotton for two growing periods.…”
Section: Irrigation and Water Deficit Impactmentioning
confidence: 99%
“…Studies have shown the biomass of cotton plants and their reproductive organs increase with the volume of irrigation [30]. Irrigation levels, with drip irrigation, affect the number of closed bolls (The quantity of irrigation influenced the count of closed bolls) [31]. The data was obtained at 4 irrigation levels and plots four varieties of cotton for two growing periods.…”
Section: Irrigation and Water Deficit Impactmentioning
confidence: 99%
“…Nitrogen is converted to N2O in the soil or in manure and usually this process becomes more intense where N reserves exceed the requirements of plants, especially under wet conditions (Oenema et al, 2005). While cotton cultivation is considered as the main cash crop for Greece, cultivation practices and their eenvironmental-friendly level are the focus of recent research (Darawsheh et al, 2020;Karydogianni et al, 2020). Research is examined the main sources for greenhouses gases in cotton cultivation.…”
Section: Introductionmentioning
confidence: 99%